Real-time qPCR for the detection of puffer fish components from Lagocephalus in food: L. inermis, L. lagocephalus, L. gloveri, L. lunaris, and L. spadiceus - Yin, Xinying; Xing, Ranran; Li, Zhiru; Hu, Bing; Yang, Lili; Deng, Ruijie; Cao, Jijuan; Chen, Ying (Frontiers in Nutrition, 2022)
Puffer fish is a type of precious high-end aquatic product, but it naturally harbors a neurotoxin known as tetrodotoxin (TTX) that is poisonous to humans and causes food poisoning. Increasing trade demand often leads to food fraud, such as adulteration of processed products with non-certified farmed wild puffer fish species. To determine the authenticity of puffer fish processed food, we developed a real-time qPCR method to detect five common puffer fish species in aquatic products: Lagocephalus inermis, Lagocephalus lagocephalus, Lagocephalus gloveri, Lagocephalus lunaris, and Lagocephalus spadiceus. The specificity, cross-reactivity, detection limit, efficiency, and robustness of the primers and probes created for five species of puffer fish using TaqMan technology have been determined. No cross-reactivity was detected in the DNA of non-target sample materials, and no false-positive signal was detected; the aquatic products containing 0.1% of a small amount of wild puffer fish materials without certification can be reliably tracked; the statistical p-value for each method's Ct value was greater than 0.05. This method can be used to validate the authenticity of wild puffer fish in aquatic products sold for commercial purposes.